On locating-chromatic number of helm graph H_m FOR 10m28 - WELYYANTI, DES; SUTANTO, DASA; YULIANTI, LYRA (Universitas Syiah Kuala, 2024)
Let G = (V,E) be a connected graph and c be a k-coloring of G. The color class S_i of G is a set of vertices given color i, for 1 i k. Let = S_1,S_2,,S_k be an ordered partition of V(G). The color code of a vertex v in (element) V(G) is defined as the ordered k–tuplec_ (v)=(d(v,S_1),d(v,S_2),...,d(v,S_k)),where d(v,S_i) = mind(v,x)| x in (element) S_i for 1 i k. If distinct vertices have distinct color codes, then c is called a locating-coloring of G. The locating-chromatic number _L (G) is the minimum number of colors in a locating-coloring of G. This paper discusses the locating-chromatic number of helm graph H_m for 10 m 28. Helm graph H_m is constructed by adding some leaves to the corresponding vertices of wheels W_m, for m 3.